2020
DOI: 10.3390/ijms21207795
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Therapeutic Potential of CCL2-Overexpressing Mesenchymal Stem Cells in Acute Stroke

Abstract: Although intravenous administration of mesenchymal stem cells (MSCs) is effective for experimental stroke, low engraftment and the limited functional capacity of transplanted cells are critical hurdles for clinical applications. C–C motif chemokine ligand 2 (CCL2) is associated with neurological repair after stroke and delivery of various cells into the brain via CCL2/CCR2 (CCL2 receptor) interaction. In this study, after CCL2-overexpressing human umbilical cord-derived MSCs (hUC-MSCs) were intravenously trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Additionally, MCP-1 is involved in neurological recovery after IS and delivers varieties of cells into the brain through MCP-1/CCR2 interplay. Moreover, after intravenous transplantation of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) with overexpression of MCP-1 in MCAO rats, angiogenesis was promoted in the ischemic penumbra region (Lee et al, 2020). This indicates that MCP-1-overexpressing hUC-MSCs distinctly repaired functional deficits in rats with MCAO by accelerating persistent increases in MCP-1 levels in brain tissue, promoting neurogenesis and angiogenesis and inhibiting neuroinflammation.…”
Section: Mcp-1mentioning
confidence: 98%
“…Additionally, MCP-1 is involved in neurological recovery after IS and delivers varieties of cells into the brain through MCP-1/CCR2 interplay. Moreover, after intravenous transplantation of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) with overexpression of MCP-1 in MCAO rats, angiogenesis was promoted in the ischemic penumbra region (Lee et al, 2020). This indicates that MCP-1-overexpressing hUC-MSCs distinctly repaired functional deficits in rats with MCAO by accelerating persistent increases in MCP-1 levels in brain tissue, promoting neurogenesis and angiogenesis and inhibiting neuroinflammation.…”
Section: Mcp-1mentioning
confidence: 98%
“…OPN expression upregulates and stimulates the migration of NSCs via CXCR4, resulting in an effective therapeutic effect after IS ( Rabenstein et al, 2015 ). During ischemia, C-C motif chemokine ligand 2 (CCL2), one of the most highly expressed chemokines, contributes to neurological repair; and the interaction between CCL2 and CCR2 (CCL2 receptor) enhances stem cell migration to the infarcted area, promoting subsequent brain repair ( Huang et al, 2018 ; Lee et al, 2020 ). TLRs are important mediators that cause neuroinflammation but are also involved in brain repair after IS.…”
Section: Protective Mechanisms Regulating Stem Cell Therapy After Ismentioning
confidence: 99%
“…Huang et al transplanted CCR2 transgenic MSCs in MCAO model animal and found that this kind of CCR2 overexpression MSCs can more effectively migrate to ischemic lesions and mediate the protection of blood-brain barrier and the more significant improvement of neural function [159]. In addition, Lee et al found that transplantation of CCL2 overexpressed MSCs resulted in a more significant increase in angiogenesis and neurogenesis and a more significant reduction in inflammatory response [160]. Moreover, the researchers also reported that overexpression of the neurogenic transcription factor neurogenin-1 can upregulate the expression of chemokine receptors CCR1, CCR2, and CXCR4 in MSCs, thus increasing the homing of MSCs to ischemic regions and promoting the further improvement of neural function [161].…”
Section: Gene Transfection or Overexpressionmentioning
confidence: 99%